2015
DOI: 10.1373/clinchem.2014.229476
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Circulating Tumor Cells in Breast Cancer

Abstract: BACKGROUND Determining the transcriptional profile of circulating tumor cells (CTCs) may allow the acquisition of clinically relevant information while overcoming tumor heterogeneity-related biases associated with use of tissue samples for biomarker assessment. However, such molecular characterization is challenging because CTCs are rare and outnumbered by blood cells. METHODS Here, we describe a technical protocol to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In this regard, Mostert et al developed a 16 gene profile assay based on qPCR mRNA expression quantification, distinguishing patients showing no response to therapy or dying in less than nine months after start of first-line systemic therapy from those with a better prognosis [58]. Moreover, Fina et al compared CTC counts with gene expression patterns based on the PAM50 gene panel in CTC from seven MBC patients resulting in no correlation between CTC number and gene expression levels as well as molecular subtype specific differences [41]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Mostert et al developed a 16 gene profile assay based on qPCR mRNA expression quantification, distinguishing patients showing no response to therapy or dying in less than nine months after start of first-line systemic therapy from those with a better prognosis [58]. Moreover, Fina et al compared CTC counts with gene expression patterns based on the PAM50 gene panel in CTC from seven MBC patients resulting in no correlation between CTC number and gene expression levels as well as molecular subtype specific differences [41]. …”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA, AKT2, TWIST1, ALDH1, EPCAM, ERBB2, MUC1 and EGFR, respectively [14, 3640]. Studies using a multimarker qPCR panel to follow up patients during the course of disease have rarely been published up to now [41]. …”
Section: Introductionmentioning
confidence: 99%
“…When coupled to high-throughput microarray or RNAsequencing technologies and unbiased bioinformatics analyses, the aforementioned obstacles are significantly surmounted (Curtis, 2015;Magbanua and Park, 2014). Overall, these new-generation studies have allowed single-cell and bulk-cell analyses of CTCs, which efficiently capture the transcriptional heterogeneity and identify the molecular portraits of metastasizing cells (Ascolani et al, 2015;Cassatella et al, 2012;De Mattos-Arruda et al, 2013;Fina et al, 2015;Lang et al, 2015;Polzer et al, 2014;Powell et al, 2012). For example, one study has demonstrated that CTCs express various biomarkers and mediators of EMT (Yu et al, 2013), a phenotypic change crucial for the completion of the metastatic cascade (Bill and Christofori, 2015;Hanahan and Weinberg, 2011;Kalluri, 2009;Kalluri and Weinberg, 2009;Radaelli et al, 2009).…”
Section: Molecular Profiling Of Circulating Tumor Cellsmentioning
confidence: 99%
“…In recent years more research oncologists are becoming interested in the mechanisms of tumor-induced lymphangiogenesis in various tumors (19,20). Breast cancer is one of the most common types of cancer among women worldwide (21,22). Over 50% of early-stage breast cancer patients have local lymph node metastasis (18).…”
Section: Introductionmentioning
confidence: 99%